Transcriptome-Wide Analysis and Functional Verification of RING-Type Ubiquitin Ligase Involved in Tea Plant Stress Resistance - Xing, Dawei; Li, Tongtong; Ma, Guoliang; Ruan, Haixiang; Gao, Liping; Xia, Tao (Frontiers in Plant Science, 2021)
The ubiquitin/26S proteasome pathway is a critical protein-degradation pathway in plant growth and development as well as in nearly all biological and abiotic stress processes. Although as a member of the ubiquitin/26S proteasome pathway, the E3 ubiquitin ligase family has been shown to be essential for the selective degradation of downstream target proteins, it has been rarely reported in tea plants (Camellia sinensis). In this study, through database searches and extensive manual deduplication, 335 RING finger family proteins were selected from the Tea Plant Information Archive. These proteins were divided into six categories by the difference of RING finger domain: RING-H2, RING-HCa, RING-HCb, RING-C2, RING-v, and RING-G. Stress-induced differential gene expression analysis showed that 53 proteins in RING finger family can respond to selected exogenous stress. In vitro ubiquitination assays indicated that TEA031033, which was named CsMIEL1, exhibited the activity of E3 ubiquitin ligases. CsMIEL1-overexpressing transgenic Arabidopsis thaliana seedlings were resistant to some exogenous abiotic stresses, such as salt and drought stress but sensitive to exogenous methyl jasmonate treatment. Furthermore, CsMIEL1 reduced the accumulation of anthocyanin in transgenic plants in response to low temperature treatment. The results of this article provide basic date for studying the role of ubiquitin/26S proteasome pathway in tea plants response to stresses.